NAMPT haploinsufficiency is a collateral lethal therapeutic vulnerability in high-risk myeloid malignancies with TP53 inactivation - Madhavi D. Senagolage; Hunter Z. Blaylock; Saira Khan; Sarah J. Skuli; Martin P. Carroll; Megan E. McNerney (Blood Neoplasia)
Abstract: Monosomy 7 (−7) and deletions of chromosome arm 7q (del(7q)) are prevalent high-risk cytogenetic abnormalities that often co-occur with del(17p) (harboring TP53). To identify novel targeted therapies based on specific vulnerabilities in high-risk myeloid malignancies, we investigated druggable, chromosome 7–encoded essential genes that are monoallelically deleted in the context of −7/del(7q), that is, collateral lethal genes. By mining genome-wide CRISPR-Cas9 screen data sets, we identified nicotinamide phosphoribosyltransferase (NAMPT) on 7q22.3 as a specific susceptibility in 81.5% of −7/del(7q) malignancies. Human acute myeloid leukemia (AML) cell lines with partial loss of NAMPT and primary samples from patients with −7 AML demonstrated heightened sensitivity to the NAMPT inhibitor KPT-9274 compared to control samples. Notably, NAMPT inhibitors were equally effective in NAMPT-deficient samples with TP53 loss. Furthermore, combining NAMPT and poly (ADP-ribose) polymerase (PARP) inhibitors, which augment DNA damage, resulted in synergistic therapeutic effects in NAMPT-deficient AML cells. These findings indicate that NAMPT heterozygosity is a therapeutic vulnerability in high-risk myeloid malignancies with −7/del(7q) and recommend NAMPT levels as a biomarker for NAMPT inhibitor sensitivity. This study also establishes a data-driven framework for identifying collateral lethal genes in cancers with recurrent chromosomal deletions.